Między ideologią i praxis. Organizacja socjalistyczna w PRL w latach 1956–1981 - Kania, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The end of World War II coincided with the beginning of the process of establishing the Polish new order whose references were the political, social and economic solutions of the USRR, while its ideological basis was Marxism interpreted by Lenin and Stalin. The establishment of the new political system in accordance with official ideology required transposing its ideas to the practical ground with practical sciences acting as a bridge between abstract thinking and reality. The subject of the following article is an analysis of the assumptions of the Polish socialist organizational studies and its connection with Marxism-Leninism in the years 1956–1981.
Keywords: organizacja socjalistyczna; badania organizacyjne; marksizm-leninizm; socjalizm; Polska Republika Ludowa; ideologia